Trace Elements in High‐Elevation Soils on Six Mountains in Maine, USA. Issue 2 (11th March 2015) - Hardy, A.; Langley‐Turnbaugh, S.J.; Murphy, D.
Abstract : Human activity, sometimes stretching back centuries, has caused short‐ and long‐range transport of trace elements. Trace elements and other pollutants exist in high‐elevation forest ecosystems due to inputs from parent material, atmospheric deposition, and bioaccumulation. This research project assessed spatial and temporal changes in trace element concentrations on six mountains in Maine. A horizon and O horizon samples were collected from different elevations on six Maine mountains. Samples were digested and analyzed for total As, Cd, Co, Cr, Cu, Mn, Ni, Pb, V, and Zn using inductively coupled plasma atomic emission spectrometry (ICP–AES). Organic horizon trace element concentrations were generally higher than those in the mineral horizons, and tended to be higher than those reported in the past. In the organic horizons trace element concentrations tended to increase with increasing elevation, but in the mineral horizons they tended to decrease with the exception of Pb. Organic horizon trace element concentrations were lowest on the northernmost mountain in the study, while mineral trace element concentrations did not exhibit any consistent geographical trends. In the organic and mineral horizons, some trace elements correlated very strongly with each other, suggesting a common source or a common retention mechanism.